2021
DOI: 10.1002/ldr.3820
|View full text |Cite
|
Sign up to set email alerts
|

Response of ammonia‐oxidizing archaea and bacteria to streptomycin sulfate and penicillin in coastal wetlands along the Bohai Rim

Abstract: Antibiotics are pollutants that are constantly discharged into ocean and coastal wetlands and affect the growth and activity of microorganisms. Ammonia-oxidizing archaea (AOA) and bacteria (AOB), which are very important in the global nitrogen cycle, are affected by antibiotics in the environment as well. Antibiotics have different influences on AOA and AOB microbial communities due to their different biochemical compositions and metabolic mechanisms, which change the ammoniaoxidizing process in different envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…All the microorganisms involved in this study were nitrifying and denitrifying microorganism. However, they responded to NH 4 + and NO 3 − differently, and some studies found that AOA amoA and AOB amoA, nirS, and nirK respond to environmental factors differently [69,73]. This study further demonstrates that even microbiota with the same nitrogen conversion gene respond significantly differently to environmental factors such as NH 4 + , NO 3 − , and antibiotics.…”
Section: Nitrogen Conversion-related Microorganismssupporting
confidence: 56%
See 1 more Smart Citation
“…All the microorganisms involved in this study were nitrifying and denitrifying microorganism. However, they responded to NH 4 + and NO 3 − differently, and some studies found that AOA amoA and AOB amoA, nirS, and nirK respond to environmental factors differently [69,73]. This study further demonstrates that even microbiota with the same nitrogen conversion gene respond significantly differently to environmental factors such as NH 4 + , NO 3 − , and antibiotics.…”
Section: Nitrogen Conversion-related Microorganismssupporting
confidence: 56%
“…It is worth noting that, except for AOA amoA, A3W2 showed significant differences in the community structures of the other three genes. Although there is a lack of direct evidence that the community structure of AOA amoA is more stable than AOB amoA under the impact of antibiotics, AOA has been found to be insensitive to antibiotics [68,69]. The results of this study show that sulfamethazine has a stronger effect on the nitrogen conversion microbial community and nitrogen conversion at a mild AWD.…”
Section: Nitrogen Conversion-related Microorganismsmentioning
confidence: 55%